Research of the Level of Emotional Intelligence of Preschool Teachers-Methodologists - Sabol, Diana M.; Melenets, Liudmyla I.; Tretyak, Olha P.; Shcherbyna, Viktoriia M.; Kulbediuk, Anastasiia Yu. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The objective of this study was to find out the level of emotional intelligence of preschool teachers-methodologists with the purpose of further professional advancement (enhancing their emotional competence). Tools applied for collecting and processing statistics were the following: survey results, methodologist’s checklists of observation of conducting classes by the teacher, N. Hall’s Emotional Intelligence Test, questionnaires for parents. There was also a survey of training participants followed by written feedback. STATA software was used for data processing, and the online TextAnalyzer utility was used to process free responses from the parent questionnaires. It is found that the system of formation of emotional intelligence, based on the training we have developed, has a positive impact on the development of emotional intelligence of preschool teachers-methodologists. The above approach enhances the knowledge of preschool teachers about their emotions, senses and feelings, contributing to the development of their ability to understand their own emotions. After the training, 7.14% of the participants showed a low level as opposed to the initial level of 33.33%. The medium level rose significantly, from 60.0% to 78.6%. And the high level of awareness of emotional intelligence in teachers has increased more than twice - from 6.67% to 14.29%. The arithmetical mean for raw scores also increased - from 43.87 to 57.54, thus confirming that the system used in training allows developing strategies for modulation of their emotions, introducing the training participants to the techniques of expression of their emotions and developing a range of emotional competency skills aimed at overcoming emotive situations. Since during the analysis of the lessons by the methodologist the teacher had to respect both the positive and negative response of the methodologist and since respect is a component of leadership, we can say that the feedback contributed to the development of leadership qualities of teachers. Regarding pedagogical skills, provided that the teacher constantly works on self-improvement of emotional intelligence, we state that the level of the teacher’s pedagogical skills also improves. We consider it reasonable to further explore the possibilities of developing the competence of emotional intelligence in future teachers during their study in higher educational institutions and preschool teachers.